H.

W NO : 5(i)
Let f i′ = αf i + 2 + βf i +1 + γ f i −1 + δ f i −2
Show that the order of accuracy is 4.

Solution
f ′( x ) = αf ( x + 2∆x ) + β f ( x + ∆x ) + γ f ( x − ∆x ) + δ f ( x − 2∆x )
Using Taylor series expansion,
f ( x + 2∆x ) = f ( x ) + 2∆xf ′( x ) +

4∆x 2
8∆x 3
16∆x 4
f ′′( x ) +
f ′′′( x ) +
f ′′′′( x ) + .......
2!
3!
4!

f ( x + ∆x ) = f ( x ) + ∆xf ′( x ) +

∆x 2
∆x 3
∆x 4
f ′′( x ) +
f ′′′( x ) +
f ′′′′( x ) + .......
2!
3!
4!

f ( x − ∆x ) = f ( x ) − ∆xf ′( x ) +

∆x 2
∆x 3
∆x 4
f ′′( x ) −
f ′′′( x ) +
f ′′′′( x ) + .......
2!
3!
4!

f ( x − 2∆x ) = f ( x ) − 2∆xf ′( x ) +

4 ∆x 2
8∆x 3
16∆x 4





f ( x) −
f ( x) +
f ′′′′( x ) + .......
2!
3!
4!

For the given expression to be valid, the following conditions must be satisfied

α + β +γ +δ = 0

(1)

2α∆x + β∆x − γ∆x − 2δ∆x = 1

(2)

2α∆x 2 + β

∆x 2
∆x 2

+ 2δ∆x 2 = 0
2
2

4
1
1
4
α∆x 3 + β ∆x 3 − γ∆x 3 − δ∆x 3 = 0
3
6
6
3
Solving (1) ,(2) ,(3) and (4)

α=

−1
12∆x

β=

2
3∆x

γ =

−2
3∆x

(3)

(4)

δ=

1
12∆x

f ′( x ) =

−1
2
−2
1
f ( x + 2∆x ) +
f ( x + ∆x ) +
f ( x − ∆x ) +
f ( x − 2∆x )
12∆x
3∆x
3∆x
12∆x

On expanding and simplifying,

f ′( x ) = f ′( x ) −

1
∆x 4 f ′′′′′( x ) + ...........
30

Order of accuracy= 4

H.W NO: 5(ii)
Let f i′′= αf i + βf i +1 + γ f i + 2 + δ f i +3
Find the order of accuracy.

Solution
f ′′( x ) = αf ( x ) + βf ( x + ∆x ) + γ f ( x + 2∆x ) + δ f ( x + 3∆x )
Using Taylor series expansion,
f ( x + ∆x ) = f ( x ) + ∆xf ′( x ) +

∆x 2
∆x 3
∆x 4
f ′′( x ) +
f ′′′( x ) +
f ′′′′( x ) + .......
2!
3!
4!

f ( x + 2∆x ) = f ( x ) + 2∆xf ′( x ) +

4∆x 2
8∆x 3
16∆x 4
f ′′( x ) +
f ′′′( x ) +
f ′′′′( x ) + .......
2!
3!
4!

f ( x + 3∆x ) = f ( x ) + 3∆xf ′( x ) +

9 ∆x 2
27 ∆x 3
81∆x 4





f ( x) +
f ( x) +
f ′′′′( x ) + .......
2!
3!
4!

For the given expression to be valid, the following conditions must be satisfied

α + β +γ +δ = 0

(1)

β∆x + 2γ∆x + 3δ∆x = 0

(2)

β

∆x 2
9
+ 2γ∆x 2 + δ∆x 2 = 1
2
2

(3)

1
4
9
β ∆x 3 + γ∆x 3 + δ∆x 3 = 0
6
3
2

(4)

Solving (1) , (2) ,(3) and (4)

α=

2
∆x 2

β=

−5
∆x 2

γ =

4
∆x 2

δ=

−1
∆x 2

f ′′( x ) =

2
−5
4
−1
f ( x ) + 2 f ( x + ∆x ) + 2 f ( x + 2∆x ) + 2 f ( x + 3∆x )
2
∆x
∆x
∆x
∆x

On expanding and simplifying,
f ′′( x ) = f ′′( x ) −

11 2
∆x f ′′′′( x ) + ...........
12

Order of accuracy = 2